A Dandy-Walker Variant Prenatally Diagnosed Using Ultrasound on One of the Fetuses of a Twin Pregnancy Obtained through In Vitro Fertilization - Dinu-Florin Albu; Cristina-Crenguta Albu; Stefan-Dimitrie Albu (International Journal of Medical Research and Review, 2015)
We present the case of a patient aged 42 years, who was sterile of undiagnosed nature and who resorted to IVF, as a last resort to get pregnant. Following this procedure, a twin pregnancy resulted. Ultrasound investigation, of the "second opinion" type performed using a Voluson E8 ultrasound 4D module highlighted: twin pregnancy 34.1 weeks old in evolution; A female fetus without visible malformations on the ultrasound, estimated weight of 2,300 g; B female fetus with borderline ventriculomegalia and vermis hypoplasia with Dandy-Walker cyst appearance, plus a rare malformation association, hypotelorism. Estimated fetal weight is 2,500 g. It is the first case described in the specialized literature of a version of Dandy-Walker syndrome prenatally diagnosed on one of the fetuses of a twin pregnancy, resulting from in vitro fertilization. The probable etiology of the malformation is genetic, hence the need for careful supervision of all high-risk pregnancies and the need of genetic counseling and consultation, with the final aim of limiting the appearance of affected newborns.